2018
DOI: 10.14260/jemds/2018/740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sudarshan Kriya on Stress Reduction in General Population

Abstract: BACKGROUND Stress, depression and anxiety have a yearly prevalence of 10 to 20% in the general population. All factors that cause one's conditions to diverge too far from the normal homeostasis lead to stress. Our attempts to restore the condition back to homeostasis also leads to stress. Stress affects quality of life by affecting the factors like level of unhappiness, focus, sleep disturbances, anger, frustration etc., because while responding to stress the sympathetic nervous system becomes active. Asthma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For analyzing immediate impact, WHO-5 Well-Being Index was administered before and after the intervention which showed a significant improvement [ Table 5 ]. Studies analyzing the impact of SK on stress levels found that regular practice improved levels of well-being, happiness, focus, and reduced anger and frustration and concluded that the life appeared “eased out.”[ 9 23 ] Other studies have shown SK to have an antidepressant like affect and also reported stabilized cortisol levels and normalization of BDNF levels. [ 8 ] Another study[ 10 ] which evaluated an improvement of depressive symptoms in ADS patients found similar results, lowering of Cortisol and ACTH levels and improvement of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…For analyzing immediate impact, WHO-5 Well-Being Index was administered before and after the intervention which showed a significant improvement [ Table 5 ]. Studies analyzing the impact of SK on stress levels found that regular practice improved levels of well-being, happiness, focus, and reduced anger and frustration and concluded that the life appeared “eased out.”[ 9 23 ] Other studies have shown SK to have an antidepressant like affect and also reported stabilized cortisol levels and normalization of BDNF levels. [ 8 ] Another study[ 10 ] which evaluated an improvement of depressive symptoms in ADS patients found similar results, lowering of Cortisol and ACTH levels and improvement of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%